Conditions for eradicating hepatitis C in people who inject drugs: A fibrosis aware model of hepatitis C virus transmission. (21st April 2016) - Rozada, Ignacio; Coombs, Daniel; Lima, Viviane D.
Abstract: It is estimated that 80% of new hepatitis C virus (HCV) infections occur among people who inject drugs (PWID). Eradicating HCV from this population is key for the complete eradication of the disease, and the advent of simple to use, high efficacy treatments could conceivably make this scenario possible. This paper presents a mathematical model where transmission of HCV is studied in a simulated population of PWID where fibrosis progression is explicitly tracked. The stability thresholds that determine whether HCV will remain endemic or become eradicated were established numerically, and analytically on a reduced version of the model. Conditions on testing and treatment rates for eradication to occur were determined, within the context of the new high efficacy therapies. The results show that HCV eradication in the PWID population of the Vancouver, BC test scenario is achievable, but testing and especially treatment rates will need to increase significantly from current rates. Parameter estimates were drawn from published data. Abstract : Highlights: We developed a deterministic compartmental model of HCV disease transmission. The model targets people who inject drugs, explicitly tracking the fibrosis level. We determined the stability of the model, both numerically and analytically. By increasing testing and treatment we could potentially eradicate the epidemic.